Aceh Tengah Racecourse - Rizqi Mardha Tillah (Jurnal Ilmiah Mahasiswa Arsitektur dan Perencanaan, 2019)
AbstractCentral Aceh Regency has many tourist attractions, one of which is horse racing, many tours from various regions of Aceh and Outside Aceh arrive. Horse racing that people often refer to as "Pacu Kude" The needs of the community in watching the match match horse obstructed due to Tribune spectators that are less extensive and insufficient so that many lovers of horse matches watch in an uncomfortable place such as on the edge of the racetrack and in the heat of the sun, in addition, many horse racing tourists are less comfortably controlled due to the lack of parking arrangements so that traffic jams and structuring of traditional shops made by community members are organized and not neat. Therefore, making a fix again at the Central Aceh Racecourse Arena designed a new racetrack that requires a high level of comfort from horse racing lovers to the racetrack, enjoying the running of the game to shopping in traditional shops. The design of the Central Aceh racetrack also looks to follow the characteristics of Central Aceh's cultural symbols in every form and appearance of the design.